Experimental Study and Analysis on Degradation of Oily Sludge from Process Equipment by Continuous Hybrid Treatment (Journal of Engineering, 2018)
It is well known that petroleum refineries are considered the largest generator of oily sludge which may cause serious threats to the environment if disposed of without treatment. Throughout the present research, it can be said that a hybrid process including ultrasonic treatment coupled with froth floatation has been shown as a green efficient treatment of oily sludge waste from the bottom of crude oil tanks in Al-Daura refinery and able to get high yield of base oil recovery which is 65% at the optimum operating conditions (treatment time = 30 min, ultrasonic wave amplitude = 60 micron, and (solvent: oily sludge) ratio = 4). Experimental results showed that 83% of the solvent used was recovered meanwhile the main water which was separated from solid particles was reused. Three types of sonic probes were used to compare effects of their amplitude created. Results revealed that beyond optimum ultrasound intensity, the treating time has an adverse effect on process efficiency. Results proved that usage 0.05% NaOH during the proposed hybrid process increased the oil recovery from 50 to 65%. The proposed hybrid treatment method could represent an environmentally friendly treatment of waste sludge produced from an oil refinery.